Cardiac Autonomic Neuropathy Predicts All-Cause and Cardiovascular Mortality in Patients With End-Stage Renal Failure: A 5-Year Prospective Study - Doulgerakis, Dimitrios (Kidney Int Rep, 2017)
INTRODUCTION: Chronic renal disease is associated with increased cardiovascular (CV) mortality. Cardiac autonomic neuropathy (CAN) is predictive of mortality for diseases that affect the autonomic nervous system. We prospectively evaluated the prognostic value of indexes of left ventricular (LV) function and CAN in all-cause and CV mortality of patients with end-stage renal failure (ESRF). METHODS: A total of 133 patients with ESRF were recruited. LV function was evaluated by echocardiography, whereas cardiac autonomic function was assessed using the battery of the 4 standardized tests proposed by Ewing. RESULTS: A total of 123 of 133 (92.5%) patients completed the study and were followed for a mean of 4.9 ± 2.6 years. Mean LV ejection fraction (LVEF) was 50.9 ± 6.9%, whereas 70 (57.9%) patients had CAN. Sixty-nine all-cause and 36 CV deaths were recorded. The survival rates at 3, 5, and 7 years were 77.2%, 57.4%, and 33.7%, respectively. Multivariate analysis after adjustment for waist circumference, current smoking, history of diabetes, and coronary artery disease demonstrated that the only independent predictors of all-cause mortality during follow-up were age, serum triglycerides, LVEF, and presence of CAN. Competing risk regression analysis, after adjusting for waist circumference, coronary heart disease, serum glucose, and triglycerides, indicated that age and presence of CAN were independent risk factors for CV mortality. DISCUSSION: Age and presence of CAN are independent predictors of all-cause and CV mortality in patients with ESRF. The functionality of the cardiac autonomic nervous system activity can be used for the risk stratification in patients with ESRF.